Mourning ruby eaudiobook - Dunmore, Helen (Recorded Books Inc., 2016)
About thirty years ago, a mother laid her newborn baby in a shoebox and left it in the backyard of an Italian restaurant. Now the baby, Rebecca, is a mother herself. A child of no one and nowhere, she has created her own unorthodox but tender family. Then this hopeful life is dealt a blow that could shatter even the strongest of ties. Now, Rebecca must face the future by delving into her mysterious past. Dunmore's most ambitious work to date, Mourning Ruby is a meditation on memory and history-both personal and public. It's an unforgettable tale of love, loss, and the transcendent power of storytelling itself